Quantificação da água interceptada pelo cafeeiro irrigado por meio de um pivô central convencional - Silva, Nara Cristina de Lima (2015)
A center pivot irrigation system was observed to determine water accumulation under the canopy of mature coffee shrub at the expense of water falling on the central region between rows. This fact is justified given the irrigation depth intercepted by what is called the shade effect. The current study describes, schematizes and experimentally proves this shade effect and considers potential savings in water and electricity that are a consequence of this phenomenon. The experiment was carried out on a 115.33 ha plantation of Coffea arabica spaced 4m x 0.7m. Half of this area was planted with the cultivar Catuai and the other half with Mundo Novo. The center pivot irrigation system had 11 towers spread out over a 608.58 m cantilevered span. The description and schematization of the \"shade effect\" were based on field observations and understanding the center pivot function via technical manuals. The \"shade effect\" was investigated using wooden structures covered by plastic sheets (150 microns thick). The structures were positioned between the spans of the last 10 towers to measure irrigation levels both under the shrub canopy and between rows. Data were analyzed by descriptive statistics and analysis of variance. It was found that irrigation depths under the plant canopies were greater and statistically different from irrigation depths between rows for both cultivars. Specifically, plant interception caused, on average, a 30.4% concentration of the irrigation depth at the outer canopy edge. There was no statistical difference between the shade effect caused by either cultivar despite a height difference of approximately 80 cm. Finally, farmers could achieve water and energy savings by adjusting irrigation timing to take advantage of the shade effect.